1981
DOI: 10.1364/ol.6.000182
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-brightness coherent radiation in the vacuum ultraviolet by four-wave parametric oscillation in mercury vapor

Abstract: Coherent radiation at several wavelengths in the vacuum ultraviolet (VUV) has been generated by four-wave parametric oscillation in mercury vapor. When a powerful ultraviolet pump laser of frequency omega(p) is tuned to a two-photon resonance, VUV signal photons at frequency omega(s), as well as idler photons at frequency omega(i), are generated such that omega(s) + omega(i) = 2omega(p). A frequency-doubled dye laser tuned to two-photon resonance with the 6s6d(1)D(2) level near 280.3 nm produced output at 184.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 9 publications
(3 reference statements)
0
11
0
1
Order By: Relevance
“…For perfect phase matching Ak = 2kp -ki -k, = 0, the generated intensity ZFwM is maximized (sinc [O] = 1). From the experimental data values of the nonlinear susceptibility for the four-wave mixing process have been determined by (1) and are given by the rhombs in Fig. 6, assuming an average intensity of 1014 W/cm2 for Z,,.…”
Section: Nm)mentioning
confidence: 99%
“…For perfect phase matching Ak = 2kp -ki -k, = 0, the generated intensity ZFwM is maximized (sinc [O] = 1). From the experimental data values of the nonlinear susceptibility for the four-wave mixing process have been determined by (1) and are given by the rhombs in Fig. 6, assuming an average intensity of 1014 W/cm2 for Z,,.…”
Section: Nm)mentioning
confidence: 99%
“…We suggest that the generation of emission near the second harmonic, in at least one of these examples, can be thought of as a resonant four-wave-mixing phenomenon [19]. The results obtained for the ls-2s two-photon resonant case could have arisen in the closed sequence of transitions 2$~co +2p 2p -+ 1$+co 1$ +2cop~2$ where co"=2cooco' is the shifted second harmonic (ignoring Rabi splitting and ac Stark effects), and co'-0.…”
Section: Resultsmentioning
confidence: 91%
“…(7) shows that the wave function evolved from the ns initial state (for n &2) has with the wave function evolved from the 1s state having a complementary form [Eq. (19) of Ref. [6] ].…”
Section: Resultsmentioning
confidence: 99%
“…In the VUV Tomkins and M a h o n 8 6 and Bokor et al 95 have reported four-wave parametric oscillation in Hg vapor. The IR results will be discussed in Section 8.3.…”
Section: -ω 3 ' ωmentioning
confidence: 98%